SEEK SOLUTIONS TO COMMUNITY PROBLEMS WITH HOLISTIC APPROACHES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 1 December 2016 Academicians in the university need to go back to the fundamentals in imparting knowledge to the public, by moving away from the confines of the 'ivory tower mentality' and towards a more holistic role, with approaches that are more inclusive and utilising the available expertise of the higher learning institutions for the benefit of the country and society.